2018
DOI: 10.1080/21691401.2018.1431648
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of oral lipid nanoparticle formulations (LNFs) for chemical stabilization of antitubercular drugs: physicochemical and cellular evaluation

Abstract: Rifampicin (RIF) and Isoniazid (INH) are two major first-line antitubercular drugs (ATDs) that are typically administered orally, in combination. However, INH-catalysed degradation of RIF under acidic pH environment of the stomach is a major concern related to its oral delivery, and is dramatically accelerated upon further exposure to and interaction with INH. This interaction, in turn, triggers a direct decline in the available RIF dose below the sub-therapeutic level, thereby diminishing its therapeutic effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…An attractive characteristic of NLC technology that makes it an intriguing delivery platform for anti-TB therapy is the ability to co-load multiple therapeutic agents of different solubilities. Banerjee et al engineered NLC loaded with rifampicin and isoniazid [125]. These dual-drug-loaded NLC achieved phago-lysosomal trafficking; data indicated that these carriers effectively co-localized with different cellular compartments (lysosome and endosome) of macrophages [125].…”
Section: Nanostructured Lipid Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…An attractive characteristic of NLC technology that makes it an intriguing delivery platform for anti-TB therapy is the ability to co-load multiple therapeutic agents of different solubilities. Banerjee et al engineered NLC loaded with rifampicin and isoniazid [125]. These dual-drug-loaded NLC achieved phago-lysosomal trafficking; data indicated that these carriers effectively co-localized with different cellular compartments (lysosome and endosome) of macrophages [125].…”
Section: Nanostructured Lipid Carriersmentioning
confidence: 99%
“…Banerjee et al engineered NLC loaded with rifampicin and isoniazid [125]. These dual-drug-loaded NLC achieved phago-lysosomal trafficking; data indicated that these carriers effectively co-localized with different cellular compartments (lysosome and endosome) of macrophages [125]. Following oral administration, the findings revealed that the formulated NLC enhanced the pharmacokinetic profile of different drugs and overall increased their relative bioavailability by many folds when compared to unformulated drugs.…”
Section: Nanostructured Lipid Carriersmentioning
confidence: 99%
“…Then the supernatant was plated in 96-well plates, and absorbance was recorded in a multimode spectrophotometer (Molecular Devices-i3X) at a wavelength of 540 nm. 22 20,23,24 Images were acquired in CLSM (Leica TCS SP8, Germany) in the respective channels under suitable magnifications. Images were analyzed using Leica Las-X software.…”
Section: Synthesis Of Osmmentioning
confidence: 99%
“…Fluorescence spectroscopy can be employed for estimating the lipophilic molecular environment of the synthesized LDC-NPs by tagging with a specific lipophilic fluorescence marker or dye (e.g., Nile red or Coumarin-6). Fluorescent lipophilic dyes those absorption bands differ in size, shape, polarity, and intensity with the surrounding molecular environmental nature [44, 45]. The intensity of the peak will get increased as the particle size gets decreased so by this one can easily compare the particle size of the tested conjugated LDC-NPs samples.…”
Section: Detailed In Vitro Physicochemical Characterizationsmentioning
confidence: 99%